﻿EASAPS/ESPRAS Considerations in getting back to work in Plastic Surgery with the COVID-19 Pandemic – A European point of view - van Heijningen, Ivar; Frank, Konstantin; Almeida, Francisco; Bösch, Urs; Bradic, Nicola; Costa, Horacio; Demirdover, Cenk; Henley, Mark; Kamolz, Lars Peter; Rouif, Michel; Spendel, Stephan; Russe-Wilflingseder, Katharina; Stark, Birgit; Giunta, Riccardo E.; Parreira, Jose Carlos; Zic, Rado (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2020)
The aim of this paper is to summarize the results of a consensus process and a European webinar of the two societies, European Association of Societies of Aesthetic Surgery (EASAPS) and the European Society of Plastic, Reconstructive and Aesthetic Societies (ESPRAS) on what is considered safe practice based on the scientific knowledge we have today. This review of the current situations gives considerations which have to be taken into account when getting back to work in plastic surgery with COVID-19 in Europe. At all times, one should be familiar the local and regional infection rates in the community, with particular emphasis on the emergence of second and third waves of the pandemic. Due to the fast-evolving nature of the COVID-19 pandemic the recommendations aim to be rather considerations than fixed guidelines and might need to be revised in near future.
Keywords: Corona Virus; Covid-19; SARS-CoV-2; Plastische Chirurgie; Pandemie